2018
DOI: 10.5380/geo.v74i1.54132
|View full text |Cite
|
Sign up to set email alerts
|

Estudo Comparativo Dos Métodos De Simulação Snesim E Filtersim - Aplicado a Um Modelo Sintético De Cobre

Abstract: ResumoOs métodos de simulação geoestatística tradicionais podem apresentar resultados inadequados quando estruturas complexas como boudins, dobras, falhas, canais meandrantes, dentre outras, precisam ser reproduzidas. Pois, para modelar estruturas complexas, o uso do variograma é limitado e para suprir esta limitação, os métodos geoestatísticos de multiponto foram propostos. Neste trabalho é apresentado um estudo comparativo em que os algoritmos de simulação multiponto (Multiple-Point Simulation -MPS) SNESIM e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
1
1
0
1
Order By: Relevance
“…In addition, it can also be found that the accuracy of the FILTERSIM algorithm simulation results is significantly higher than that of the SNESIM algorithm. This shows that the FILTERSIM algorithm simulation results are more representative, which is the same as the research conclusions of Takafuji et al [23]. The new method has two typical characteristics: (1) The MPS simulation results are captured from two training images surrounding the subregions.…”
Section: Comprehensive Example-3d Strata Reconstructionsupporting
confidence: 79%
See 1 more Smart Citation
“…In addition, it can also be found that the accuracy of the FILTERSIM algorithm simulation results is significantly higher than that of the SNESIM algorithm. This shows that the FILTERSIM algorithm simulation results are more representative, which is the same as the research conclusions of Takafuji et al [23]. The new method has two typical characteristics: (1) The MPS simulation results are captured from two training images surrounding the subregions.…”
Section: Comprehensive Example-3d Strata Reconstructionsupporting
confidence: 79%
“…The flowchart is shown in Figure 1 When reconstructing a three-dimensional copper ore model, Takafuji et al compared the performance of SNESIM algorithm and FILTERSIM (Filter-based simulation) algorithm. The results showed that the FILTERSIM algorithm simulation results showed better spatial continuity, and it was more representative than the SNESIM algorithm simulation results [23]. Because the FILTERSIM algorithm replaces the simulated grid with the most similar training pattern as a whole or locally, it ensures continuity of the simulation results.…”
Section: Introductionmentioning
confidence: 89%
“…Para a construção das realizações foi utilizado o método Single Normal Equation Simulation (SNESIM). O SNESIM é um algoritmo de simulação multiponto (Multiple-Point Simulation -MPS) que simula variáveis categóricas e, a fim de reproduzir padrões, varre uma imagem de treinamento calculando a probabilidade de ocorrência de cada um dos padrões possíveis, que são guardados em árvores de busca (24), permitindo assim a construção de múltiplas realizações. Este método também permite condicionar as realizações aos dados de poços.…”
Section: Construção Das Realizações De Fraturasunclassified